2018
DOI: 10.1111/beer.12191
|View full text |Cite
|
Sign up to set email alerts
|

Constructing gender identity through masculinity in CSR reports: The South Korean case

Abstract: Drawing on the themes of men and masculinity, this article examines texts in the corporate social responsibility (CSR) reports of local multinational enterprises (MNEs) in South Korea, an emerging economy. This article explores how Korean male hegemony is hidden and naturalized in CSR reporting. Focusing on the discursive construction of gender identity, we analyze how CSR reports portray gendered identities in ways that may foster gender inequality by examining how the texts reflect the inferior position of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…Another avenue to extend this research would be to investigate if masculinity is connected to the observed voluntarism. The prevailing hegemonic masculinity of business (Griffin, 2013;Lee & Parpart, 2018) may play a role for both the conventional marginalisation of social groups outside of a hegemonic power structure, and for the marginalising of criticism that I observe. By giving evidence of justification fallacies, I want to open up for the possibility that companies frequently fail in justifying their activities, and inspire research to investigate corporate acts of justification.…”
Section: Discussion Limitati On S and Future Re S E Archmentioning
confidence: 90%
See 1 more Smart Citation
“…Another avenue to extend this research would be to investigate if masculinity is connected to the observed voluntarism. The prevailing hegemonic masculinity of business (Griffin, 2013;Lee & Parpart, 2018) may play a role for both the conventional marginalisation of social groups outside of a hegemonic power structure, and for the marginalising of criticism that I observe. By giving evidence of justification fallacies, I want to open up for the possibility that companies frequently fail in justifying their activities, and inspire research to investigate corporate acts of justification.…”
Section: Discussion Limitati On S and Future Re S E Archmentioning
confidence: 90%
“…Second, there is research providing direction on the impact disclosure has on legitimacy (Cormier & Magnan, 2015) and on financial performance (Lawal, May, & Stahl, 2017). Another dimension of disclosure is the focus on specific issues, for example, environment (Delgado-Márquez, Pedauga, & Cordón-Pozo, 2017), gender-equality issues (Lee & Parpart, 2018), or data (Schultz & Seele, 2020). My present interest lies in disclosure of one broad issue, CSR activities.…”
mentioning
confidence: 99%
“…Another study on the sustainability reports of selected Fortune 500 companies reports that “discourses on women and gender carry the traditional patriarchal notions and women were presented as a distressed species and companies tried to portray themselves as the saviors of women” (Hossain et al , 2017a, p. 262). Exploring the inherently embedded meaning of texts in the CSR reports of 15 Korean Multinational Enterprise, Lee and Parpart (2018) note that women’s voices are silenced and marginalized in the CSR reports. Similarly, Ben-Amar et al (2020) report that Canadian corporations strategically use “merit” and “diversity” to obfuscate the exact representation of women on the corporate board.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On one hand, these programmes represent awareness of women’s systemic oppression and exploitation; on the other, they reflect women as human capital, a resource for international agencies, governments and corporations (Prügl, 2015; Tornhill, 2019). Women are simultaneously positioned as victims and saviours, with implications for how men are situated in development (Cornwall et al, 2011) and corporate responsibility narratives (Lee and Parpart, 2018). Who is included in worker empowerment programmes, and how they are portrayed, reproduces the persistent, damaging norms that inflect the production of ‘correct’ roles and behaviours of women and men within systems of differentiation that uphold the hegemony of men.…”
Section: Researching the Hegemony Of Men In Labour Governance Mechanisms: A Frameworkmentioning
confidence: 99%